Digital transformation in business and management research: An overview of the current status quo. (April 2022) - Kraus, Sascha; Durst, Susanne; Ferreira, João J.; Veiga, Pedro; Kailer, Norbert; Weinmann, Alexandra
Abstract: It is no surprise that research on digital transformation (DT) has raised vast interest among academics in recent decades. Countries, cities, industries, companies, and people all face the same challenge of adapting to a digital world. The aim of the paper is twofold. First, map the thematic evolution of the DT research in the areas of business and management, because existing research in these areas to date has been limited to certain domains. To achieve this, articles were identified and reviewed that were published in the Chartered Association of Business Schools' (ABS) ≥ 2-star journals. Based on these findings, the second objective of this paper will be to propose a synergistic framework that relates existing research on DT to the areas of business and management, which will help form the evolutionary perspective taken in this paper. Considering the emerging development of the topic under investigation, the framework is understood as a sound basis for continued discussion and forthcoming research. Highlights: This article maps the thematic evolution of current research on digital transformation in business and management. 217 articles from leading business and management journals are analyzed using diverse methodological procedures. A synergistic framework linking current research on digital transformation with business and management is proposed.